Analisis Faktor-Faktor Yang Mempengaruhi Fiscal Stress - Septira, Finky; Prawira, Ida Farida Adi (Universitas Pendidikan Indonesia, 2019)
AbstractThis study aims to find out how the influence of regional own revenue growth, growth in capital expenditure, and economic growth that is proxied by GDRP influences fiscal stress in Sumatera-based districts and cities in 2014-2016. The population of this study is the district/city government in Sumatera Island which consist of 154 district/ cities. The sample selection was determined based on purposive sampling criteria so that 106 districst/cities governments were sampled in this study. This study uses secondary data in the form Realization of Regional Revenue and Expenditure (LRA APBD) as well as data is in the form of data on Domestic Regional Products and Gross (GDRP). Hypotesis testing tools in this study using E-views 9. From the results of the test, researcher found that the growth of regional own revenue and economic growth that is proxied by GDRPaffect fiscal stress while the growth of capital expenditure does not affect fiscal stress. Keywords. Capital Expenditure; Economic Growth; Fiscal Stress; PDRB; Regional Own Revenue. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh pertumbuhan pendapatan asli daerah (PAD), pertumbuhan belanja modal, dan pertumbuhan ekonomi yang diproksikan dengan PDRB berpengaruh terhadap fiscal stress pada kabupaten dan kota se-Sumatera tahun 2014-2016. Populasi penelitian ini adalah pemerintah daerah kabupaten /kota di Pulau Sumatera yang terdiri dari 154 kabupaten/kota. Pemilihan sampel ditentukan berdasarkan kriteria purposive sampling sehingga didapatkan 106 pemerintah kabupaten/kota yang menjadi sampel dalam penelitian ini. Penelitian ini menggunakan data sekunder berupa Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah (LRA APBD) serta data berupa data Produk Regional Domestik dan Bruto (PDRB). Alat uji hipotesis dalam penelitian ini menggunakan software Eviews 9. Dari hasil pengujian didapatkan bahwa pertumbuhan PAD dan pertumbuhan ekonomi yang diproksikan dengan PDRB berpengaruh terhadap fiscal stress sedangkan pertumbuhan belanja modal tidak berpengaruh terhadap fiscal stress. Kata Kunci. Belanja Modal; Fiscal Stress; Pendapatan Asli Daerah; PDRD; Pertumbuhan Ekonomi.